(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lake Garais is the second deepest lake in Latvia. Its maximum depth is 56.0 meters, but its average depth is 16.5 meters. Lake Geranimovas-Ilzas is the fifth deepest lake in Latvia. Its maximum depth is 46.0 meters, but its average depth is 9.8 meters [13]. During the research of Lake Gernimovas-Ilzas and Lake Garais three zooplankton groups have been found, i.e. Rotatoria, Cladocera and Copepoda. Having analysed the quality composition of species the authors have concluded that the pollution level of these lakes is low, because there are such olygosoprobic zooplankton species as Keratella cochlearis, Keratella quadrata, Filinia longiseta, that die from lack of oxygen in few hours.